VD_FINDINFO HC / 2018 / 873 vom 15. Oktober 2018 - VD Tribunal cantonal (2018)
CONTRAT DE TRAVAIL, RÉSILIATION IMMÉDIATE, JUSTE MOTIF, TÉMOIN, APPRÉCIATION DES PREUVES | 8 CC, 337 al. 1 CO, 337c al. 1 CO, 337c al. 2 CO, 337c al. 3 CO, 157 CPC (CH), 169 CPC (CH)